Design, Synthesis, and Evaluation of Lipopeptide Conjugates of Mercaptoundecahydrododecaborate for Boron Neutron Capture Therapy. (27th February 2019) - Isono, Aoi; Tsuji, Mieko; Sanada, Yu; Matsushita, Akari; Masunaga, Shinichiro; Hirayama, Tasuku; Nagasawa, Hideko
Abstract: We developed new 10 B carriers for boron neutron capture therapy (BNCT) that can effectively transport and accumulate boron clusters into cells. These carriers consist of a lipopeptide, mercaptoundecahydrododecaborate (BSH), and a disulfide linker. The carriers were conceived according to the structure of pepducin, a membrane‐penetrating lipopeptide targeting protease‐activated receptor 1 (PAR1). To improve the membrane permeability of BSH, the structure was optimized using various lipopeptides possessing different peptides and lipid moieties. These synthesized lipopeptides were conjugated with BSH and evaluated for intracellular uptake using T98G glioblastoma cells. Among them, the most effectively incorporated and accumulated in the cells was compound5 a, which contains a peptide of 13 residues derived from the intracellular third loop of PAR1 and a palmitoyl group. For further improvement of 10 B accumulation in cells, the introduction of an amine linker was investigated; intracellular uptake similar to that of5 a was observed for compound14, which has a piperazine linker. Both compounds5 a and14 showed a stronger radiosensitizing effect than BSH along on T98G cells under mixed‐neutron beam irradiation. The results demonstrate that lipopeptide conjugation is effective for enhancing intracellular delivery and accumulation of BSH and improving the cytotoxic effect of BNCT. Abstract : Across the plasma membrane : We successfully developed new 10 B carriers for boron neutron capture therapy (BNCT), which can efficiently transport and accumulate anionic boron clusters into cells using the optimized lipopeptide vehicle. The lipopeptide conjugates significantly improved the cytotoxic effect of BNCT.